An Individualized Recommendation for Controlled Ovary Stimulation Protocol in Women Who Received the GnRH Agonist Long-Acting Protocol or the GnRH Antagonist Protocol: A Retrospective Cohort Study - Chen, Ming-Xing; Meng, Xiang-Qian; Zhong, Zhao-Hui; Tang, Xiao-Jun; Li, Tian; Feng, Qian; Adu-Gyamfi, Enoch Appiah; Jia, Yan; Lv, Xing-Yu; Geng, Li-Hong; Zhu, Lin; He, Wei; et al. (Frontiers in Endocrinology, 2022)
Background: Which control ovarian stimulation (COS) protocol (GnRH agonist long-acting protocol or GnRH antagonist protocol) elicits a higher live birth rate for IVF/ICSI patients with different ages, different ovarian reserves and different body mass index (BMI)? Methods: This is a retrospective cohort study of 8579 women who underwent the first IVF-ET from January 2018 to August 2021. Propensity Score Matching (PSM) was used in data analysis to balance the baseline and improve the comparability between two protocols. Results: After PSM, significant higher live birth rates were found in the GnRH agonist long-acting protocol compared to the GnRH antagonist protocol (44.04% vs. 38.32%) (p=<0.001). Stratified analysis showed that for those with AMH levels between 3 ng/ml and 6 ng/ml (normal ovarian reserves), with BMI ≥ 24 kg/m2 and were aged ≥ 30 years old, and for those women with BMI < 24kg/m2 and age ≥30 years whose AMH levels are ≤ 3ng/ml, the GnRH agonist long-acting protocol had a higher live birth rate than the antagonist protocol [OR (95%CI), 2.13(1.19,3.80)], [OR (95%CI), 1.41(1.05,1.91)]. While among women with BMI ≥ 24kg/m2 and age ≥30 years whose AMH levels are ≤ 3ng/ml, the GnRH agonist long-acting protocol had a lower live birth rate than the antagonist protocol [OR (95%CI), 0.54(0.32,0.90)]. However, among women with normal ovarian reserve, with BMI ≥ 24 kg/m2 and with age < 30 years and for those with normal ovarian reserve, regardless of age, are non-overweight (BMI < 24 kg/m2), the two protocols had similar live birth rates [OR (95%CI), 1.06(0.60,1.89)], [OR (95%CI), 1.38(0.97,1.97)], [OR (95%CI), 0.99(0.72,1.37)]. Among the women with AMH levels ≤ 3 ng/ml and with age < 30years, regardless of BMI, the two protocols had similar live birth rates [OR (95%CI), 1.02(0.68,1.54)], [OR (95%CI), 1.43(0.68,2.98)]. Moreover, among the participants with abnormal AMH levels (AMH levels ≥ 6ng/ml), the two protocols had similar live birth rates [OR (95%CI),1.42(0.75,2.69)], [OR(95%CI),1.02(0.19,5.35)], [OR(95%CI), 1.68(0.81,3.51)], [OR (95%CI), 0.51(0.10,2.55)]. Conclusions: The suitability of the GnRH agonist long-acting protocol or the GnRH antagonist protocol to infertility patients is dependent on specific biological characteristics of the patients.